2016
DOI: 10.1515/aoas-2015-0089
|View full text |Cite
|
Sign up to set email alerts
|

Food-Borne Pathogens and Contaminants in Raw Milk – A Review

Abstract: the aim of the present review is to highlight the threats to human health posed by consumption of milk and dairy products. the interest in drinking raw milk has been growing in some societies as many people believe it has health benefits. Raw milk is promoted as 'health food' despite the fact that it poses a realistic microbiological hazard for the consumers' health or life. Food-borne disease outbreaks associated with Campylobacter spp., Salmonella spp., shigatoxin-producing Escherichia coli, Brucella meliten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 108 publications
0
34
0
Order By: Relevance
“…In summarizing information on analytical methods for STC in foodstuffs, Veršilovskis and de Saeger [19] concluded that LC/MS/MS should be used in efforts to develop sensitive methods and that sample preparation should be improved. This was realized in some new methods developed for the determination of STC in various grains and cheese by Veršilovskis et al (LOD 0.03–0.15 μg/kg) [20,35] and in the multi-mycotoxin method reported by Sulyok et al (LOD 0.4 μg/kg) [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summarizing information on analytical methods for STC in foodstuffs, Veršilovskis and de Saeger [19] concluded that LC/MS/MS should be used in efforts to develop sensitive methods and that sample preparation should be improved. This was realized in some new methods developed for the determination of STC in various grains and cheese by Veršilovskis et al (LOD 0.03–0.15 μg/kg) [20,35] and in the multi-mycotoxin method reported by Sulyok et al (LOD 0.4 μg/kg) [29].…”
Section: Discussionmentioning
confidence: 99%
“…STC exhibits various toxicological, mutagenic, and carcinogenic effects in animals, and it has been recognized as a 2B carcinogen (possible human carcinogen) by the International Agency for Research on Cancer [17]. Recent reviews described the occurrence of STC in a variety of foodstuffs [18,19,20]. The European Food Safety Authority (EFSA) Panel on Contaminants in the Food Chain (CONTAM Panel) analyzed a total of 1259 samples of cereal grains, cereal products, and nuts, collected between August 2013 and November 2014 in nine European countries (and originating from 45 countries), for the presence of STC.…”
Section: Introductionmentioning
confidence: 99%
“…There are less yeast and mold in raw milk than LAB [64]. In a study conducted in Slovenia, 95.0% of raw milk that was collected during winter and summer contains yeast and 63.3% contains molds.…”
Section: Fungal Contaminants and Mycotoxins In Conventional Animal Prmentioning
confidence: 99%
“…In general, it is not expected that milk has microorganisms and toxins unless there is a systemic or local infection. But clinical and subclinical mastitis, which are associated with local or systemic infections are common problems for animals [64,65]. The milk flora of dairy animals consists of lactic acid bacteria (LAB; Lactococcus, Lactobacillus, Leuconostoc, Streptococcus, Enterococcus spp.)…”
Section: Bacterial Contaminants In Conventional Animal Productsmentioning
confidence: 99%
See 1 more Smart Citation